Mixed Type Procedure Model or Adversarial Law? - Nachkebia, Giorgi (European Scientific Journal, ESJ, 2017)
By introducing the Criminal Procedure Code, amendments were made in the criminal legislation of Georgia and the mixed type model of the Criminal Procedure Law was transformed into the Anglo-American model of the Criminal Procedure Law. It turned out that this transformation was not properly analyzed. As a result the adversarial criminal procedure law was developed which was grounded on the Anglo-American procedure rules and does not recognize any exceptions. In the modern world majority of highly cultured countries which stay within the scope of the international criminal law choose mixed type model of criminal procedure law and stand apart from inquisitorial and adversarial process. Accordingly, modernization of the Criminal Procedure Code is high on agenda for Georgian legislators. I hope that the presented article will prove the necessity of the measures that should be taken to improve the abovementioned.